2014
DOI: 10.1111/jcpp.12229
|View full text |Cite
|
Sign up to set email alerts
|

Relative immaturity and ADHD: findings from nationwide registers, parent‐ and self‐reports

Abstract: Relative immaturity compared to class mates might contribute to ADHD diagnosis and pharmacotherapy despite absence of parallel findings in reported ADHD symptom loads by relative immaturity. Increased clinical awareness of this phenomenon may be warranted to decrease risk for imprecise diagnostics and treatment. We speculate that flexibility regarding age at school start according to individual maturity could reduce developmentally inappropriate demands on children and improve the precision of ADHD diagnostic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
70
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(83 citation statements)
references
References 35 publications
9
70
2
1
Order By: Relevance
“…3 Although this study confirms a relative age effect, there have been mixed findings from other countries with low prescribing rates. [14][15][16][17] It is possible that this discrepancy reflects our specific focus on the receipt of ADHD diagnosis whereas studies from Nordic countries which did not find a consistent relative age effect used medication data as the ADHD outcome. 14,15 In both boys and girls, we found a greater cumulative incidence of clinically diagnosed ADHD amongst younger children within the school-year.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…3 Although this study confirms a relative age effect, there have been mixed findings from other countries with low prescribing rates. [14][15][16][17] It is possible that this discrepancy reflects our specific focus on the receipt of ADHD diagnosis whereas studies from Nordic countries which did not find a consistent relative age effect used medication data as the ADHD outcome. 14,15 In both boys and girls, we found a greater cumulative incidence of clinically diagnosed ADHD amongst younger children within the school-year.…”
Section: Discussionmentioning
confidence: 86%
“…The term 'ADHD' for 'hyperkinetic disorder' has also been used in previous Nordic studies that use the ICD classification. 16,20,21 The PRC is a digital national archive containing basic information on Finnish citizens and permanent residents. Individual data filed in the register contains, for example, name, personal identity code, citizenship, date of birth/death and emigration/immigration (as noted above, both the source population and ADHD cases were children born in Finland).…”
Section: Case Identification and Registersmentioning
confidence: 99%
See 1 more Smart Citation
“…This concern was amplified when various large-scale international studies noted an association between birth date and ADHD or ADHD medication (Elder 2010;Evans, Morrill and Parente 2010;Halldner et al 2014;Morrow et al 2012;Zoega, Valdimarsdóttir, and Hernández-Diaz 2012). According to these studies, younger children in a year group are much more likely to be diagnosed with ADHD and be prescribed ADHD medication than are elder children in a year group.…”
Section: Introductionmentioning
confidence: 93%
“…Several studies (Elder, 2010; Evans, Morrill, & Parente, 2010; Halldner et al, 2014; Morrow et al, 2012; Zoëga, Valdimarsdóttir, & Hernández-Díaz, 2012) showed that relative age is a significant determinant of ADHD diagnosis and treatment. Overall, the youngest children in class are twice as likely as their classmates to receive a diagnosis of ADHD and medication.…”
Section: Birth Month Mattersmentioning
confidence: 99%